2017
DOI: 10.1111/cen.13327
|View full text |Cite
|
Sign up to set email alerts
|

Measuring TSH receptor antibody to influence treatment choices in Graves’ disease

Abstract: TSH receptor antibody (TRAb) plays a key role in the pathogenesis of Graves' disease (GD), and its levels correlate with the clinical course. The second- and third-generation TRAb assays have >95% sensitivity and specificity for the diagnosis of GD and have improved the utility of TRAb to predict relapse. TRAb levels decline with antithyroid drug (ATD) therapy and after thyroidectomy. Its level increases for a year following radioactive iodine (RAI) therapy, with a gradual fall thereafter. TRAb level >12 IU/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…TRAb is a hallmark of GH. It is a diagnostic marker of the disease [20], a prognostic marker of relapse after remission [7, 21], and a risk marker of developing Graves' orbitopathy [22]. With the present study we confirmed that TRAb was a prognostic marker and showed that patients with lower TRAb were at higher risk of overtreatment (elevated TSH).…”
Section: Discussionsupporting
confidence: 81%
“…TRAb is a hallmark of GH. It is a diagnostic marker of the disease [20], a prognostic marker of relapse after remission [7, 21], and a risk marker of developing Graves' orbitopathy [22]. With the present study we confirmed that TRAb was a prognostic marker and showed that patients with lower TRAb were at higher risk of overtreatment (elevated TSH).…”
Section: Discussionsupporting
confidence: 81%
“…Thyrotropin receptor autoantibody showed the highest sensitivity and specificity for diagnosing the disease. 31 , 32 The increasing sensitivity of TRAb is mainly because of its destructive role in the pathophysiological mechanism involved in the disease. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The CD74 SNP rs2569103 was located within the upstream region of CD74 and showed the strongest association with the disease, making it a possible target for transcription factors. Indeed, the putative transcription factor-binding sites were predicted using PROMO [ 32 , 33 ]. At SNP rs2569103, the A allele generates motifs for nuclear receptor subfamily 3, group C, member 1 (NR3C1) (TC A GG), whereas the G allele generates a motif for forkhead box P3 (FOXP3) (GTTTC G ).…”
Section: Resultsmentioning
confidence: 99%